THE USE OF SOCIAL MANAGEMENT IN THE DECONSTRUCTION OF MANAGERIAL CONSERVATIVEISM IN PUBLIC POLICIES - Luiz Xavier da Costa, Diego; Fernandez Gomes, Edvando (Revista Gênero e Interdisciplinaridade, 2021)
In the present work we address the topic of social management, concerning its usage in the deconstruction of managerial conservatism in Brazilian public policies. Therefore, this study also aims to present that managerialism is the most predominant administrative side in public management nowadays, by exposing its rationality and characteristics, and pointing social management as a contraposition to this system. The research revealed that although managerialist approach has modernized state administration and provided notable improvements in public management, its political project draws on an excluding and elitist ideology, that favors the economic sector and constantly neglects the field of social projects in public policies. In this context, social management appears as an alternative to the neoliberal political project, which is the main component of the managerialist current, with a corporate political project where future prospects for the public management must be linked to social participation derived from a communicative rationality in which democracy acquires new contours. In this sense, this work aims to comprehend how social management is employed to deconstruct managerial conservatism in public policies. This is a bibliographic research and is based on several renowned authors and researchers in the area of public and social management such as Fenando Guilherme Tenório, Alan Ferreira de Freitas, Alair Ferreira de Freitas, Marco Aurélio Marques Ferreira,Ana Paula Paes de Paula among others, that from a reading of Jürgen Habermas collaborated to an understanding of this issue.